Intertekstualni vidiki kronotopa uboja na hišnem pragu pri Ivu Andriću in Gabrielu Garcíi Márquezu v luči semiotike kulture - Košničar, Sofija P. (Primerjalna književnost, 2014)
The unexplored chronotope of a murder at the doorstep in the novels Omer-Pasha Latas by Ivo Andrić and Chronicle of a Death Foretold by Gabriel García Márquez has been compared and culturally considered in a semiotic key of the theory of semiosphere from the aspect of intertextuality. The research interest is also pointed to the rhetorical-dramaturgical aspects of chronotope, which is surprisingly similar in two Nobel Prize winners.
Keywords: Andrić, Ivo, 1892-1975; García Márquez, Gabriel, 1927-2014; srbska književnost; kolumbijska književnost; semiotika kulture; medbesedilnost; kronotop; umor; Umor of Bulgaria